Central pharmacokinetics of levodopa: Lessons from imaging studies. Issue 1 (1st October 2014) - Stoessl, A. Jon; Fahn, Stanley; Poewe, Werner
Abstract Functional imaging may be particularly helpful for the assessment of levodopa (l‐dopa) response and long‐term complications of therapy in Parkinson's disease. Radiotracer imaging allows the quantitative determination of regional changes in blood flow and glucose metabolism, as well as alterations in brain connectivity and network activation and changes in dopamine receptors, non‐dopaminergic neurotransmitter systems, and to a lesser extent, signaling pathways downstream to dopamine receptors. The focus of the present article, however, is the application of positron emission tomography (PET) to study the central pharmacokinetics of l‐dopa. Radioligands with limited affinity for the dopamine D2 receptor are sensitive to changes in the levels of synaptic dopamine and can accordingly provide helpful insights into the magnitude and time course of dopamine release after l‐dopa. Prolonged fluorodopa PET scans can be used to estimate the rate of dopamine turnover. Studies performed with these techniques have demonstrated increased dopamine turnover and increased but shorter duration release of dopamine after l‐dopa as Parkinson's disease (PD) progresses, increased release of dopamine in patients with l‐dopa–induced dyskinesia, and that aberrant patterns of dopamine release may actually predict the future development of motor fluctuations. Taken together, the studies provide in vivo validation for the hypothesis that pulsatile stimulation of dopamine receptors plays a critical role in the emergence of long‐term motor complications of therapy. Similar approaches can be used to study the non‐motor complications of PD and its treatment. © 2014 International Parkinson and Movement Disorder Society